MicroRNA-223 inhibits neutrophil extracellular traps formation through regulating calcium influx and small extracellular vesicles transmission - Liao, Tsai-Ling; Chen, Yi-Ming; Tang, Kuo-Tung; Chen, Po-Ku; Liu, Hung-Jen; Chen, Der-Yuan (Scientific reports, 2021)
Modulation of miRNAs and neutrophil extracellular traps (NETs) formation are both implicated in inflammatory disorders. Adult-onset Still’s disease (AOSD) is a systemic autoinflammatory disease with neutrophilic leukocytosis and unknown etiology. Although the NETs formation is elevated in AOSD patients, the regulatory roles of miRNAs in NETs formation in AOSD remains unclear. We revealed that the circulating levels of IL-18, NETs, and miR-223 were significantly higher in active AOSD patients, compared with inactive AOSD patients or healthy controls ( P < 0.005). Moreover, IL-18 increased calcium influx into neutrophils, which led to mitochondrial ROS (mROS) production and NETs formation. Elevated levels of NETs-DNA could induce miR-223 expression in neutrophils through activating Toll-like receptor 9. The upregulated miR-223 expression in neutrophils suppressed mROS production by blocking calcium influx, and subsequently inhibited IL-18-mediated NETs formation. Besides, the increased neutrophil-derived exosomal miR-223 levels were observed in active AOSD patients compared with healthy controls ( P < 0.005). Our in vitro assays demonstrated that the neutrophil-derived small extracellular vesicles carried miR-223, which could repress IL-18 production in macrophages. Together, these results suggest a fine-tuned mechanism between inflammatory (IL-18 induced NETs) and anti-inflammatory (miR-223) factors in AOSD. MiR-223, mROS inhibitors, and calcium channel blockers are the potential therapeutics for autoinflammatory diseases such as AOSD.